This preview shows page 1. Sign up to view the full content.
Unformatted text preview: _xk+l = _(x k . x) = (_xk) . X + xk-x = kx k-l . X + xk . 1 = kxk + xk = (k + l)xk dx dx dx dx as required. By the Principle of Mathematical Induction, we conclude that the formula is correct for all n 2: 1. r 1 -X 2r + 1 1 _ x4 34. When n = 1, rr;=l (1 + x 2 ) = 1 + x 2 and 2 = --2 = 1 + x 2 and so the formula is I-x I-x correct. Now suppose that k 2: 1 and the result is true for n = k; that is, suppose k 2k+1 II( 1 2r)=I-x +x 1 2 -x r=l We must prove that it is correct for n = k + 1; that is, we must prove that k+l Now II (1 + x2r) r=l k = (II (1 + x2r)) (1 + X 2k + 1 ) r=l 2 k + 1 -_ (11-_Xx2 ) (1 + x 2k + 1 ) (by the induction hypothesis) as required. By the Principal of Mathematical Induction, we conclude that the formula is correct for all n 2: 1....
View Full Document
- Summer '10
- Graph Theory